1998
DOI: 10.1046/j.1365-2567.1998.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin VH gene sequence analysis of spontaneous murine immunoglobulin‐secreting B‐cell tumours with clinical features of human disease

Abstract: The 5T series of multiple myelomas (MM) and Waldenstrsöm's macroglobulinaemia-like lymphomas (WM), which developed spontaneously in ageing mice of the C57BL/KaLwRij strain, shows clinical and biological features that closely resemble their corresponding human diseases. In order to compare the patterns of somatic mutation in VH genes of mouse tumours with those of human counterparts, we have determined and analysed sequences of immunoglobulin VH genes in five cases of murine MM, two of WM and one of biclonal be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The 5T33MM-VDJ sequence differed slightly (only three nucleotides) from the published sequence 19 ( Figure 1). …”
Section: Detection Of Isotype-switch Variants In 5t2mm and 5t33mm Bonmentioning
confidence: 73%
See 1 more Smart Citation
“…The 5T33MM-VDJ sequence differed slightly (only three nucleotides) from the published sequence 19 ( Figure 1). …”
Section: Detection Of Isotype-switch Variants In 5t2mm and 5t33mm Bonmentioning
confidence: 73%
“…The Ig heavy chain sequence expressed by the 5T2MM and 5T33MM tumour cells has already been published. 19 Tumour-specific primers and probes were designed in the CDR1 and the CDR3 region: 5T2MM-CDR1 sense primer: 5Ј CAC-AAC-TGC-TTG-GAA-TGC-AGT-G 3Ј; 5T2MM-CDR3 probe: 5Ј CCG-CCT-GGT-TTG-CTT-ACT-GG 3Ј; 5T33MM-CDR1 sense primer: 5Ј CAC-TAA-TTA-CTT-GAT-AGA-GTG-G 3Ј and 5T33MM-CDR3 probe: 5Ј GCA-GTT-ACC-ATA-AGC-CTC-TC 3Ј. 5T2MM and 5T33MM myeloma-related sequences were amplified using the specific CDR1 primers together with different Ig constant region-specific primers: C : 5Ј GCT-CTC-GCA-GGA-GAC-GAG-GGG-GA 3Ј; C␥: 5Ј GCG-AAT-TCC-CTT-GAC-CAG-GCA-TCC 3Ј and C␣: 5Ј CTC-GGA-TCC-TCA-CAT-TCA-TCG-TGC-C 3Ј.…”
Section: Detection Of Ig Isotype-switch Variantsmentioning
confidence: 99%
“…For the detection of the 5T2 V H sequences (Zhu et al, 1998) a PCR was performed making use of an antisense FR4 primer (5′-GGGGGATCCTGCAGAGACAGTGACCAGAGT) in combination with a sense FR1 primer (5′-GGGGGATCCACAGATCCAG-TTGGTGCAGT) in a 25 µl reaction containing: 2 mM magnesium chloride, 0.2 mM dNTP, 0.6 µM of each primer and 1.25 U Taq polymerase (Gibco, Life Technologies). Forty PCR cycles were applied after a 5 min incubation at 94°C with the following steps: 30 s at 94°C, 30 s at 55°C and 30 s at 72°C.…”
Section: Pcr Analysismentioning
confidence: 99%
“…23,24 Cytogenetic and molecular genetic analyses of these murine myelomas have shown that they closely resemble human myelomas. [25][26][27] We reported previously that when 5T33 myelomaderived 5TGM1 cells are inoculated intravenously in syngeneic or bg-nu-xid mice, they home almost exclusively to the skeleton and infrequently to the spleen. 28 Expansion within these sites results in radiographically detectable lytic bone lesions, markedly elevated serum titers of the monoclonal paraprotein, and splenomegaly.…”
mentioning
confidence: 99%